Medical image analysis of 3D CT images based on extension of Haralick texture features - Tesař, Ludvík; Shimizu, Akinobu; Smutek, Daniel; Kobatake, Hidefumi; Nawano, Shigeru (Computerized medical imaging and graphics, 2008)
new approach to the segmentation of 3D CT images is proposed in an attempt to provide texture-based segmentation of organs or disease diagnosis. 3D extension of Haralick texture features was studied calculating co-occurrences of all voxels in a small cubic region around the voxel. RESULTS: For verification, the proposed method was tested on a set of abdominal 3D volumes of patients. Statistically, the improvement in segmentation was significant for most of the organs considered herein. CONCLUSIONS: The proposed method has potential application in medical image segmentation, including diagnosis of diseases.
Keywords: Imaging, Three-Dimensional; počítačová rentgenová tomografie; Sensitivity and Specificity; senzitivita a specificita; Humans; Algorithms; rozpoznávání automatizované; Radiographic Image Enhancement; umělá inteligence; lidé; reprodukovatelnost výsledků; Artificial Intelligence; vylepšení rentgenového snímku; Reproducibility of Results; Tomography, X-Ray Computed; Pattern Recognition, Automated; Radiographic Image Interpretation, Computer-Assisted; algoritmy; zobrazování trojrozměrné; rentgenový obraz - interpretace počítačová; rentgendiagnostika břicha; Radiography, Abdominal